Dose‐Dependent Cannabidiol‐Induced Elevation of Intracellular Calcium and Apoptosis in Human Articular Chondrocytes. Issue 12 (26th August 2019) - Winklmayr, Martina; Gaisberger, Martin; Kittl, Michael; Fuchs, Julia; Ritter, Markus; Jakab, Martin
ABSTRACT: Cannabidiol (CBD) is the most abundant non‐psychoactive compound of Cannabis sativa extracts. Cannabinoids have been shown to exhibit anti‐inflammatory, analgesic, antioxidant, neuroprotective, and anti‐tumorigenic effects. In the present study, we investigated the effects of CBD on human articular chondrocytes. Cell viability was determined by Resazurin assays. Apoptosis was analyzed by annexin‐V/7‐actinomycin D (7‐AAD) staining followed by flow cytometry. Caspase 3/7 activity was measured with caspase assays. Intracellular Ca 2+ ([Ca 2+ ] i ) was monitored by time‐lapse fluorescence imaging. The perforated whole‐cell patch‐clamp technique was used for measuring the cell membrane potential. Erk1/2 phosphorylation was assessed by western blot analysis. The chondrocyte cell line C28/I2 and primary chondrocytes showed a reduced viability after treatment with concentrations of CBD greater than 4 µM. This apoptotic effect was accompanied by an increase of caspase 3/7 activity and an increase in the early apoptotic cell population. CBD elevated [Ca 2+ ] i, which was accompanied by depolarization of the cell membrane potential. The increase of [Ca 2+ ] i was abrogated, when Ca 2+ was omitted from the bath solution, indicating an influx of extracellular Ca 2+ . The cannabinoid receptor 1 (CB1) antagonist AM251 inhibited the Ca 2+ influx triggered by CBD. Preincubation with AM251 reduced the toxic effects of CBD. By looking for mediators of the apoptotic CBD effect downstream of the CB1 receptor, enhanced Erk1/2 phosphorylation could be detected after CBD treatment. However, this Erk1/2 activation proved to be unaffected by CB1 receptor blockage. The present study demonstrates that CBD promotes apoptosis and [Ca 2+ ] i elevation in human articular chondrocytes via a CB1‐receptor‐mediated mechanism. © 2019 The Authors. Journal of Orthopaedic Research ® published by Wiley Periodicals, Inc. on behalf of Orthopaedic Research Society J Orthop Res 37:2540–2549, 2019